2015
DOI: 10.1016/j.rfe.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

An inverted U‐shaped crude oil price return‐implied volatility relationship

Abstract: We examined the return–volatility relationship for USO ETF oil price return and CBOE Crude Oil ETF Volatility Index, OVX. The data for the USO and OVX covers the period covering May 11, 2007 to February 28, 2013. Our OLS regression results suggest evidence of regular feedback and leverage effects. When we employ linear quantile regression techniques, we find evidence of regular and inverse feedback effects. The inverse feedback effects being noticeable in the upper quantile region of the oil return distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 107 publications
9
22
0
Order By: Relevance
“…Low (2004) had already suggested that the cause of the asymmetric effect of the return-volatility relation could be behavioral. In the same sense, other studies provide evidence of this asymmetric relation betwen return and implied volatility (see, for example, Agbeyegbe, 2015;Badshah, 2013). …”
Section: The Return-volatilily Relationmentioning
confidence: 64%
See 3 more Smart Citations
“…Low (2004) had already suggested that the cause of the asymmetric effect of the return-volatility relation could be behavioral. In the same sense, other studies provide evidence of this asymmetric relation betwen return and implied volatility (see, for example, Agbeyegbe, 2015;Badshah, 2013). …”
Section: The Return-volatilily Relationmentioning
confidence: 64%
“…Second, the relation of the variables presents a parabola format, with the concavity upwards, different from the results for Low (2004). On the other hand, Agbeyegbe (2015) tested the nonlinear relation between the variables using conditional copula and quantile regression methods. His results identified an inverted "U" through quantiles for the relation between USO and OVX.…”
Section: The Return-volatilily Relationmentioning
confidence: 99%
See 2 more Smart Citations
“…Energy financialization also provides new research ideas and directions for the study of price behavior, risk contagion mechanisms and risk management in the energy market. The price behavior characteristics of energy financialization in the energy market mainly manifest through four aspects: volatility (Ma, Ji, and Pan 2019b;Zavadska, Morales, and Coughlan 2018), uncertainty (Agbeyegbe 2015;Liu, Ji, and Fan 2017), complexity (Zhang, Ji, and Kutan 2019) and infectivity (Ji, Liu, and Fan 2019a;Mahadeo, Heinlein, and Legrenzi 2019).…”
Section: Guest Editors' Introduction New Challenge and Research Develmentioning
confidence: 99%